Eutrophication status assessment in the Laizhou Bay, Bohai Sea: Further evidence for the ecosystem degradation. (August 2022) - Wei, Yuqiu; Cui, Hongwu; Hu, Qingjing; Bai, Ying; Qu, Keming; Sun, Jun; Cui, Zhengguo
Abstract: Laizhou Bay is plagued by many environmental problems (e.g., acidification and eutrophication) that are likely to increase in the coming decades along with social and demographic trends. We thus conducted 12 cruises from July 2019 to December 2021 in the Laizhou Bay to evaluate the potential influences of human activities on its eutrophication status. The results showed that the parameters of dissolved inorganic nitrogen (DIN) and oxygen (DO) exceeded the water quality standard in some cases during the past 3 years, suggesting DIN and DO were the crucial factors controlling water quality in the bay. Meanwhile, DIN was identified as a major pollutant in the region, and played an important role in driving the phytoplankton dynamics. Furthermore, with the increases in human-related nutrient inputs (especially DIN), the bay environment reached the mild eutrophication level and was probably at risk from excessive nutrient loads at present, further evidencing the ecosystem degradation. Highlights: DIN and DO were key factors controlling the water quality of Laizhou Bay. DIN was identified as a major pollutant in the bay. The bay environment reached the mild eutrophication level.